Towards developing a web application with text filtering for FTMSK : A case study for electronic exchange board / Sumardi Shukor - Shukor, Sumardi (2006)
The Internet is the most disembedded media as it is the most removed from face-to-face-communication. In Internet communication we do not have the limitations of space. There are no borders for circulation and there is unlimited memory space for content. This dimension of disembedding constitutes the globalisation of the medium. On the other hand, Internetbased communication has increased opportunities to secure information in a manner that has not been available up to now. This project purpose is to suggest the usage of filtering system as a mean of information filtering in the Electronic Exchange Board for FTMSK. The traditional filtering mechanism in the Electronic Exchange Board might not be able to distinguish the offensive words that have been masked. Hence, this study is conducted to identify potential techniques can be used to mask the offensive words and a new textual filtering algorithm will be developed to resolve this problems. Most of the identified masking techniques can be detected by this new filtering algorithm. However, it can never successful entirely because people will always find new ways to mask the offensive words. Therefore, there should be an authorized person whose job is to monitor and determine which postings can be allowed and not in Electronic Exchange Board.